2007
DOI: 10.1016/j.pediatrneurol.2006.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Stroke in Children

Abstract: Hemorrhagic stroke accounts for approximately half of stroke in childhood. Unlike arterial ischemic stroke, there are no consensus guidelines to assist in the evaluation and treatment of these children. We review the literature on the evaluation, treatment, etiology and neurologic outcome of hemorrhagic stroke in children. Important differences between pediatric and adult hemorrhage are highlighted, as treatment guidelines for adults may not be applicable in all cases. Needed future research and potential ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 81 publications
3
62
0
12
Order By: Relevance
“…25 The absence of hemorrhagic stroke was notable, given that hemorrhagic stroke is estimated to account for approximately half of all childhood stroke with hematologic abnormalities reported as the major risk factor in most series. 26 Similar to HGPS, children with Moyamoya also most commonly experience ischemic stroke. 27 It has not yet been established whether stroke in HGPS results from the progressive cerebral arteriopathy, narrowing and/or occlusion of the arteries within the neck, emboli arising from atheromatous plaque within arteries of the neck, emboli arising from a cardiac source, or a combination of the aforementioned processes.…”
Section: Stroke In Hgpsmentioning
confidence: 99%
“…25 The absence of hemorrhagic stroke was notable, given that hemorrhagic stroke is estimated to account for approximately half of all childhood stroke with hematologic abnormalities reported as the major risk factor in most series. 26 Similar to HGPS, children with Moyamoya also most commonly experience ischemic stroke. 27 It has not yet been established whether stroke in HGPS results from the progressive cerebral arteriopathy, narrowing and/or occlusion of the arteries within the neck, emboli arising from atheromatous plaque within arteries of the neck, emboli arising from a cardiac source, or a combination of the aforementioned processes.…”
Section: Stroke In Hgpsmentioning
confidence: 99%
“…48 Retrospective analyses have identified the leading causes In children with varicella, the first year post-infection represents the high risk window for stroke occurrence.…”
Section: Hemorrhagic Strokementioning
confidence: 99%
“…[6][7][8] Studies in adults have identified radiological features that are associated with haemorrhagic presentation and future haemorrhage. [9][10][11] Similar studies on AVM in children are, however, scarce and mostly based on studies from Europe and North America.…”
Section: Introductionmentioning
confidence: 99%